2015
DOI: 10.1068/b130192p
|View full text |Cite
|
Sign up to set email alerts
|

Planning Support in Estimating Green Housing Opportunities for Different Socioeconomic Groups in Nanjing, China

Abstract: The sustainable city concept is often criticized for being unaffordable for the majority. To cater for various socioeconomic groups, it is essential that planners consider both affordability and sustainability. We provide planners with a methodology for estimating green housing potential for various socioeconomic groups in Nanjing, China, with reference to their green housing preferences and budgets. Results indicate that under the current situation the lower-middle class can barely afford a green apartment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…High dependence on public policies for planning implementation. The sustainable city concept is often criticized for being unaffordable for the majority (Hu et al, 2015). At present, China's policies on building greening are predominantly encouraging, advocating, and expressing desirability.…”
Section: Discussionmentioning
confidence: 99%
“…High dependence on public policies for planning implementation. The sustainable city concept is often criticized for being unaffordable for the majority (Hu et al, 2015). At present, China's policies on building greening are predominantly encouraging, advocating, and expressing desirability.…”
Section: Discussionmentioning
confidence: 99%
“…The United State Environmental Protection Agency define GB as an ecologically accountable building that taps the earth's limited and renewable resource towards providing a habitable building [16]. Simply, GB is a building planned to reduce energy consumptions and emissions thus improving energy efficiency and conserving water through the adoption of nontoxic and durable materials in construction [17], obtained through renewable sources [18]. Hence, they are environment-friendly, resource-efficient buildings, comfortable to live in and providing good indoor and outdoor quality [19] and serving as a solution to environmental challenges including global climate change [20], [21] [22] confirm that the essence of a green project is life sustainability.…”
Section: Green Building and Indigenous Sustainable Architecturementioning
confidence: 99%
“…It should also be noted that the result of participation is strongly related to the predisposition of a community to use these ICT tools (Soligno et al., 2015). Chinese scholars (e.g., Cheng, 2013; Deng et al., 2014; Hu et al., 2015) have also suggested that collaborative planning and public participation through the Internet and social media have an increasingly vital influence on planning practice and theory in China. They showed that stakeholders can participate in planning and also connect and communicate with each other in the participation process through social networks.…”
Section: Literature Reviewmentioning
confidence: 99%